2016
DOI: 10.4012/dmj.2014-330
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microtensile bond strength of self-etching adhesives on normal and caries-affected dentin

Abstract: The purpose of this study was to evaluate the µTBS (microtensile bond strength) of currently available self-etching adhesives with an experimental self-etch adhesive in normal and caries-affected dentin, using a portable hardness measuring device, in order to standardize dentin Knoop hardness. Normal (ND) and caries-affected dentin (CAD) were obtained from twenty human molars with class II natural caries. The following adhesive systems were tested: Mega Bond (MB), a 2-step self-etching adhesive; MTB-200 (MTB),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
1
16
0
2
Order By: Relevance
“…A range of factors, including the structural, physical and chemical characteristics of substrate, might affect the bonding effectiveness of an adhesive system (Bahari et al, 2014;Marshall et al, 1997;Pinna et al, 2015;Shibata et al, 2016). Minimally invasive treatment of cavitated dentin lesions is based on preservation of caries-free tissue but might leave limited cariesaffected tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A range of factors, including the structural, physical and chemical characteristics of substrate, might affect the bonding effectiveness of an adhesive system (Bahari et al, 2014;Marshall et al, 1997;Pinna et al, 2015;Shibata et al, 2016). Minimally invasive treatment of cavitated dentin lesions is based on preservation of caries-free tissue but might leave limited cariesaffected tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Organic nature of dentin and its higher humidity relative to enamel makes bonding to this hard tissue very difficult 2 . Compared to SD, bonding to CAD is characterized by the lower bond strength and inferior quality of the hybrid layer 10 . Owing to these discrepancies, the bonding efficacy of different adhesive systems with SD and CAD was extensively studied 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Bonding to CAD is characterized by lower bond strength and inferior hybrid layer quality compared to bonding to SD, irrespective of the type of adhesive systemsemployed 10 . For the etch-and-rinse adhesives, discrepancies between the demineralization level and the extent of resin monomer infiltration have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the main bonding substrates for direct resin composite restorations are not normal dentin, but caries-affected dentin (CAD), after removal of the caries-infected dentin. However, it has been reported that the mechanical properties of CAD, such as tensile bond strength and hardness 1) , are inferior to those of sound dentin 2) . Since the bond strength of normal dentin decreases in the long term 3) , it has been thought that the durability of CAD bond strength is also decreased.…”
Section: Introductionmentioning
confidence: 99%